PENERAPAN SISTEM INFORMASI MANAJEMEN DALAM MENUNJANG PELAYANAN DAN ADMINISTRASI GEREJA - Simatupang, Wilson; Jhon Kristopel Manalu; Darwis Manalu (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The development of information technology has brought significant changes in various sectors, including religious organizations such as the church. The church, as a non-profit organization, requires an effective information management system to support services, administration, and decision-making. Management Information Systems (MIS) play a crucial role in integrating congregational data, finances, services, and church activities in a structured and accurate manner. This study aims to analyze the implementation of Management Information Systems in churches and its benefits in improving administrative efficiency and service quality. The method used is a literature study and descriptive analysis. The results of the study indicate that the implementation of MIS in churches can enhance work effectiveness, information transparency, and support more precise decision-making.